Synthesis and Mesomorphic Properties of New Side Chain Liquid Crystalline Oligomers Containing Salicylaldimine Mesogenic Groups - Gulbas, Hulya Elmali; Ocak, Hale; Gursel, Yesim Hepuzer; Bilgin-Eran, Belkiz (TAYLOR & FRANCIS LTD, 2013)
New liquid crystalline salicylaldimine-based homopolymers PLC1 and PLC2 have been synthesized from their corresponding monomers 5-(10-undecenyloxy)-2-[[(4-(hexyloxy)phenyl)imino]methyl]phenol (LC1 ) and 5-(10-undecenyloxy)-2-[[(4-(hexyl)phenyl)imino]methyl]phenol (LC2 ) via free radical polymerization. The polymers were characterized by 1H-NMR, differential scanning calorimetry (DSC) and optical microscopy in polarized light (polarizing microscope). The synthesized polymers have low molecular weights, and so are in the oligomeric domain. The oligomers behave very similarly to their monomers that exhibit smectic mesophases. Replacing the hexyloxy chain by a hexyl chain of the mesogenic unit generates an additional SmC mesophase in the temperature range of both the monomer and oligomer. All the observations suggest that the oligomerization of the liquid crystalline salicylaldimine monomers gives rise to decreased transition temperatures whereas it has no influence on the type and stability of the mesophase formed.
Keywords: Salicylaldimine mesogens; side chain liquid crystalline oligomers; POLYMERS; COMPLEXES; BASE; DERIVATIVES; COPOLYMERS; SERIES; ALKOXY; Chemistry; Crystallography; Materials Science